Social Classes and Digital Divide Among University Students - Bizjak Ferjan, Maruša; Ferjan, Marko; Bernik, Mojca (Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0, 2025)
In this paper, we address the phenomenon of the digital divide among students. The digital divide refers to inequalities in access to and ability to use digital technology, which are also linked to an individual's social status. As the level of digital competences varies among students, our research was interested in the factors that cause the digital divide among students. To this end, a survey of 298 students was conducted.. We used the "European Digital Competence Framework for Citizens: DigComp 2.1" to measure digital competencies and Goldthorpe's social class schema for social class. Our sample analysis found that: (1) There are statistically significant differences in mean digital competency levels between males and females for 15 out of 21 digital competency items. (2) There is no correlation between parental education and students' level of digital competencies. (3) There is a (very weak) correlation between the father's social class (or occupation) and the level of digital competencies of students for 7 out of 21 digital competency items.